Impact of Rhamnolipid Biosurfactants on Chemical Composition, Rheology, and Imbibition Performance of Crude Oils - Harry Budiharjo Sulistyarso; Indah Widiyaningsih; Yulius Deddy Hermawan; Joko Pamungkas; Sayoga Heru Prayitno (Testing Center for Oil and Gas LEMIGAS, 2025)
The application of biosurfactants in enhanced oil recovery (EOR) has generated significant interest owing to their biodegradability, low toxicity, and effectiveness in modifying oil–rock–brine interactions. Rhamnolipids—glycolipid biosurfactants synthesized by bacterial species—exhibit a distinctive amphiphilic structure that can alter the characteristics of crude oil at both molecular and macroscopic levels. This study offers a novel integrative evaluation of rhamnolipid-induced alterations in chemical composition, rheological properties, and imbibition efficacy of medium and light crude oils. The study utilizes gas chromatography–mass spectrometry (GC–MS) to clarify compositional changes in hydrocarbon fractions, viscosity assessments to measure rheological alterations in oil-biosurfactant mixtures, IFT measurements, and spontaneous imbibition experiments to analyze wettability changes and recovery efficacy. This study simultaneously examines compositional, viscosity, IFT, and capillarity-driven displacement mechanisms across two distinct crude oil categories, contrasting with prior research that focused solely on either compositional or interfacial properties within a single crude oil type, thereby offering comparative insights into biosurfactant–hydrocarbon interactions. The results are anticipated to enhance comprehension of biosurfactant-mediated enhanced oil recovery mechanisms, refine rhamnolipid application methodologies, and connect molecular-level alterations with core-scale oil recovery efficacy. This integrated method provides a novel framework for customizing biosurfactant formulations to particular crude oil varieties, thus improving recovery while preserving environmental sustainability.